2020
DOI: 10.36644/mlr.119.3.america
|View full text |Cite
|
Sign up to set email alerts
|

America's Paper Prisons: The Second Chance Gap

Abstract: Over the last decade, dozens of states and the federal government have enacted “second chance” reforms that increase the eligibility of individuals arrested, charged, or convicted of crimes to shorten their sentences, clear their criminal records, and/or regain the right to vote. While much fanfare has accompanied the increasing availability of “second chances,” little attention has been paid to their delivery. This study introduces the concept of the “second chance gap,” which it defines as the difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Our analyses revealed that 35% of cases had no disposition, and 75% of people had at least one such case on their record. Missing data may severely limit the potential benefits of automatic relief legislation, and leave a persistent “second chance gap” (Chien, 2020). If cases with missing dispositions are excluded from dismissal, few people will receive a clean slate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our analyses revealed that 35% of cases had no disposition, and 75% of people had at least one such case on their record. Missing data may severely limit the potential benefits of automatic relief legislation, and leave a persistent “second chance gap” (Chien, 2020). If cases with missing dispositions are excluded from dismissal, few people will receive a clean slate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, McElhattan's work (2021) highlights that "The pursuit of harshly punitive policies has often come without commensurate investment in administrative infrastructure, thereby intensifying the pains of punishment for criminalized subjects" (McElhattan, 2021). Without improving data and reporting systems, automatic relief reforms may exclude many people eligible for relief or delay the process (Chien, 2020). The burden will fall on either state and county agencies to investigate missing data, or on people with criminal records to navigate the time-consuming, bureaucratic procedures to correct their record, defeating the purpose of automatic relief (Lageson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations